Multiple Scale Music Segmentation Using Rhythm, Timbre, and Harmony. (16th November 2006) - Jensen Jensen, Kristoffer Kristoffer
Abstract : The segmentation of music into intro-chorus-verse-outro, and similar segments, is a difficult topic. A method for performing automatic segmentation based on features related to rhythm, timbre, and harmony is presented, and compared, between the features and between the features and manual segmentation of a database of 48 songs. Standard information retrieval performance measures are used in the comparison, and it is shown that the timbre-related feature performs best.